1992
DOI: 10.1073/pnas.89.21.10449
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-crystallin can function as a molecular chaperone.

Abstract: The a-crystallins (aA and aB) are major lens structural proteins of the vertebrate eye that are related to the small heat shock protein family. In addition, crystallins (especially aB) are found in many cells and organs outside the lens, and aB is overexpressed in several neurological disorders and in cell lines under stress conditions. Here I show that a-crystallin can function as a molecular chaperone. Stoichiometric amounts of aA and aB suppress thermally induced aggregation of various enzymes. In particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
1,213
5
16

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,699 publications
(1,250 citation statements)
references
References 48 publications
16
1,213
5
16
Order By: Relevance
“…In protein refolding assays in vitro (Horwitz, 1992; Jakob et al ., 1993), aggregation prevention by the ATP‐independent small HSPs has been shown to occur independent of the ATP‐dependent HSP70 machinery, but for efficient refolding, substrate transfer to the HSP70 machine is required (Lee & Vierling, 2000; Mogk et al ., 2003). Also, in living cells, refolding assistance by HSPB1 was found to require a functional HSP70 machinery (Bryantsev et al ., 2007), and in this study, a similar scenario was found to be true for the best refolding stimulating D. melanogaster small HSP, CG14207.…”
Section: Discussionmentioning
confidence: 99%
“…In protein refolding assays in vitro (Horwitz, 1992; Jakob et al ., 1993), aggregation prevention by the ATP‐independent small HSPs has been shown to occur independent of the ATP‐dependent HSP70 machinery, but for efficient refolding, substrate transfer to the HSP70 machine is required (Lee & Vierling, 2000; Mogk et al ., 2003). Also, in living cells, refolding assistance by HSPB1 was found to require a functional HSP70 machinery (Bryantsev et al ., 2007), and in this study, a similar scenario was found to be true for the best refolding stimulating D. melanogaster small HSP, CG14207.…”
Section: Discussionmentioning
confidence: 99%
“…The small heat shock protein α-crystallin, which is the major protein of the mammalian lens, is an aggregate assembled from two polypeptides (αA and αB). Each polypeptide has a molecular weight around 20,000 kDa and these structural proteins are known to act as molecular chaperones (Horwitz, 1992). Both proteins appear to have extensive nonlens roles (Nagineni and Bhat, 1992).…”
Section: Mitochondrial Protective and Repair Systemsmentioning
confidence: 99%
“…Among the molecular chaperones, α-crystallins are utilized during protein synthesis and to prevent aggregation of misfolded or damaged proteins during oxidative stress (Horwitz, 1992). Loss of chaperone activity occurs in ocular tissues following a significant decrease in the crystallin content (Kapphahn et al, 2003).…”
Section: Introductionmentioning
confidence: 99%